Impact of the COVID-19 pandemic on growth determinants in premature neonates: observational study in a secondary health service in Carapicuíba, São Paulo (2020–2023) - Martha, Vanessa Marques Leite; Masquio, Deborah Cristina Landi; Santos, Luiz Silva dos; Martha, Julia Marques Leite; Martha, Pedro Marques Leite; Colares Neto, Guido de Paula (Frontiers in Pediatrics, 2024)
Introduction: Prematurity is a factor that contributes to the increase in infant morbidity and mortality and is associated with factors determining child growth, such as nutritional deficits, mainly during the COVID-19 pandemic. Objective: To evaluate the factors determining the growth of premature neonates treated at a secondary health service during the COVID-19 pandemic. Method: Observational retrospective and prospective cohort study of premature patients followed at the follow-up clinic in the municipality of Carapicuíba from February 2020 to December 2023. Through a review of medical records, anthropometric data were collected from birth to corrected gestational age, approximately six months, and nutritional and non-nutritional data with direct or indirect influence on growth. Statistical analysis with tests for quantitative and qualitative variables was carried out with the SPSS Statistics software version 27.0 (SPSS et al.,USA). Result: The study analyzed a sample of 302 newborns, predominantly male (51.7%) and classified as moderately preterm (47.4%), with an average gestational age of 32.4 ±2.8 weeks. Prenatal complications occurred in 59.3% of cases, while neonatal complications, such as extrauterine growth restriction (EUGR, 30.8%) and use of parenteral nutrition (36.1%), were common, with an average hospital stay of 30.2±26.1 days. Most newborns were artificially fed (51%) Moreover, they received multivitamins (71.9%). At six months, the newborns showed healthy growth with an average weight of 6718.2 ±1346.5g. Multiple linear regression analysis revealed significant associations between EUGR and negative Z scores for weight, length, and head circumference at six months. Complications such as anemia and congenital abnormalities also negatively impacted these scores. Comparatively, the newborns in the group pre-vaccination against COVID-19 had more significant growth at six months and more prevalence of newborns born large for gestational age (LGA), while complications such as gastroesophageal reflux disease and viral bronchiolitis was more common in the post-vaccination group. Conclusion: During the COVID-19 pandemic, non-nutritional factors, especially EUGR, significantly influenced the anthropometry of premature babies. This condition highlighted the need for more effective therapeutic strategies and public health measures to improve the growth and development of premature infants.